Reliable Integration of Thermal Flow Sensors into Air Data Systems - Viana, Felipe; Torres, Frank Sill (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2018: Anais do VIII Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2018)
Having in mind its impact on the security of air flight applications, there is a high demand for robust and reliable airspeed measurement systems. Thermal flow sensors are a recent proposal in order to circumvent the critical limitations of classic airspeed sensors and have the potential to considerably enhance the security of future aircrafts. This paper is a step towards the application of these sensors and explores how existing state-of-the-art reliability techniques can be applied for this new class of devices. Therefore, a detailed simulation model of a thermal flow sensors is setup in a redundant manner and widely applied voting mechanism are added to the system. Using extensive fault simulations, we explored the applicability of each mechanism for different fault classes and determined the most reliable solution. Results indicate that not the most complex but a more simpler method based on median estimation shows the highest robustness for this new kind of airspeed sensors.